2006
DOI: 10.1113/jphysiol.2006.115352
|View full text |Cite
|
Sign up to set email alerts
|

N‐acetylcysteine attenuates the decline in muscle Na+,K+‐pump activity and delays fatigue during prolonged exercise in humans

Abstract: Reactive oxygen species (ROS) have been linked with both depressed Na + ,K + -pump activity and skeletal muscle fatigue. This study investigated N -acetylcysteine (NAC) effects on muscle Na + ,K + -pump activity and potassium (K + ) regulation during prolonged, submaximal endurance exercise. Eight well-trained subjects participated in a double-blind, randomised, crossover design, receiving either NAC or saline (CON) intravenous infusion at 125 mg kgfor 15 min, then 25 mg kg −1 h −1 for 20 min prior to and thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
215
1
5

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 231 publications
(261 citation statements)
references
References 58 publications
15
215
1
5
Order By: Relevance
“…No tecido muscular esquelético, a oxidação de glutationa excede a capacidade intracelular de reoxidação, resultando em aumento na razão glutationa oxidada/glutationa reduzida (1,3,4) . Nessas condições, o fígado aumenta a liberação de glutationa para o sangue, elevando a captação e a capacidade antioxidante do tecido muscular durante o processo de contração.…”
Section: Artigo De Revisão O Glicogênio Como Regulador Da Produção Deunclassified
See 2 more Smart Citations
“…No tecido muscular esquelético, a oxidação de glutationa excede a capacidade intracelular de reoxidação, resultando em aumento na razão glutationa oxidada/glutationa reduzida (1,3,4) . Nessas condições, o fígado aumenta a liberação de glutationa para o sangue, elevando a captação e a capacidade antioxidante do tecido muscular durante o processo de contração.…”
Section: Artigo De Revisão O Glicogênio Como Regulador Da Produção Deunclassified
“…Dessa forma, estamos propondo neste estudo, um mecanismo metabólico adicional, pelo qual o aumento da produção de espécies reativas de oxigênio aceleraria os processos de fadiga durante contrações musculares intensas. Quando a oxidação de glutationa é baixa, grande parte da glutationa oxidada produzida no tecido muscular pode ser rapidamente regenerada pelo sistema glutationa redutase/NADPH + (3,4,24) . Porém, alterações do balanço redox para um estado mais oxidado pode comprometer a capacidade desse sistema, favorecendo a ocorrência de estresse oxidativo (2,3,7,26) .…”
Section: Artigo De Revisão O Glicogênio Como Regulador Da Produção Deunclassified
See 1 more Smart Citation
“…NAC also reduces oxidative burst activity but enhances phagocytosis in rodent and human neutrophils [13,17]. NAC is particularly suitable for the attenuation of oxidant-mediated injury as it not only has a direct antioxidant effect by means of free-radical scavenging properties but also replenishes depleted cellular glutathione stores restoring intrinsic cellular antioxidant defenses [6,13,32,50]. The widely accepted use of NAC in current clinical practice confers an additional advantage for its potential use in the context of CS, IRI, or trauma, as the toxicity profile of the drug is well established and clinicians already are experienced in its use.…”
Section: Introductionmentioning
confidence: 99%
“…It may provide an alternative to phosphorylation of the NKA or associated FXYD because the pump's subunits contain residues that can be oxidized (e.g. the sulfhydryl group) [12] and it has been shown that NKA in skeletal muscle is redox sensitive [13]. Bibert et al [12] recently showed that angiotensin II induces PKC activity and that leads to ROS generation, which subsequently causes glutathionylation of the b subunit and hence inhibits NKA activity.…”
Section: Introductionmentioning
confidence: 99%